Party Quotas and Rising Women Politicians in Singapore. Issue 1 (17th March 2015) - Tan, Netina
Abstract : Women were severely underrepresented in Singapore's early politics. From 1970 to 1984, not a single female member was found in the Parliament. Unlike the experiences of Taiwan and South Korea in this issue, the ruling People's Action Party (PAP) of Singapore faced no similar pressure from the opposition parties or feminist groups to adopt gender quotas to "fast track" women into politics (Dahlerup and Freidenvall 2005). Yet, the total number of women candidates increased from 0 in 1980 to 32 by 2011. And women's legislative representation reached a high of 23% after the 2011 general election.